Porosity mapping of extrudate snacks based on X-ray images - Abhinawa Damar; Samodra Ailsa Saraswati; Karyadi Joko Nugroho Wahyu; Nugraha Bayu (BIO Web of Conferences)
Extruded snacks are popular food products, but their quality depends on extrusion process such as temperature and moisture content. Understanding how these conditions affect the microstructure and porosity of extrudates can help improve quality control. Conventional methods for measuring porosity in extrudates are destructive. Non-destructive methods like X-ray computed tomography (CT) scanning could characterize porosity while preserving samples. This study used X-ray CT scanning and image analysis to characterize the microstructure and porosity of extruded corn-bean snacks produced under different extrusion temperatures and moisture contents. Snacks were produced by extruding a mixture of corn grits and bean flour at 120°C or 140°C barrel temperature and 14% or 18% feed moisture. The extrudates were scanned by X-ray CT, and Avizo software was used to reconstruct 3D images and quantify porosity. Lower moisture extrudates exhibited higher porosity up to 67% and pore volume up to 7000 mm3. Grayscale values correlated to measured porosity allowed the creation of a porosity colormap. X-ray CT scanning non-destructively characterized microstructure and porosity differences between extrudates produced under different conditions. The image analysis techniques could be applied for quality evaluation of extruded snacks.